TEACHING SENIOR SCHOOL STUDENTS - STRATEGIES FOR WORKING WITH HYPERACTIVE STUDENTS AT SCHOOLS FOR GIFTED CHILDREN - Kudritskaya, M.I.; Kopeikina, L.N.; Mikhalkova, N.M.; Budilova, Y.M. (Publisher of Kostanay Regional University named after Akhmet Baitursynuly, 2025)
The article defines Special Educational Needs (SENs) and explains the increasing importance of inclusive education. The diversity among SEN learners is highlighted, focusing on the underestimated needs of hyperactive students. The problem stated in the article reflects the common challenges that educators face in teaching and supporting hyperactive students, as their needs are often overshadowed by overtly disruptive behaviors. The research purpose presented in the article is to synthesize research-informed strategies that empower teachers to support hyperactive students, enhancing their participation, engagement, and academic success.
Keywords: special educational needs; hyperactive students; strategies to support hyperactive students; teaching gifted students; attention span; motivation for learning